Effect on quality of life of cisplatin added to single-agent chemotherapy as first-line treatment for elderly patients with advanced non-small cell lung cancer: Joint analysis of MILES-3 and MILES-4 randomised phase 3 trials. (July 2019) - Morabito, Alessandro; Piccirillo, Maria Carmela; Maione, Paolo; Luciani, Andrea; Cavanna, Luigi; Bonanno, Laura; Filipazzi, Virginio; Leo, Silvana; Cinieri, Saverio; Morgillo, Floriana; Burgio, Marco Angelo; Ferrara, Domenica; et al.
Highlights: Adding cisplatin to single-agent chemotherapy does not prolong OS in elderly NSCLC. This paper reports that cisplatin does not improve quality of life. A significant worsening of some toxicity-related scales was found. Abstract: Objectives: To evaluate the effect on quality of life (QOL) of the addition of cisplatin to single-agent chemotherapy in the treatment of elderly patients with advanced non-small cell lung cancer (NSCLC) enrolled in two parallel phase 3 trials, MILES-3 and MILES-4. Patients and methods: Advanced NSCLC pts, >70 years old, performance status (PS) 0–1, were eligible. Patients were randomly assigned to chemotherapy without or with cisplatin. EORTC QLQ C30 and LC13 questionnaires were planned at baseline, end of cycle 1 and end of cycle 2 in both trials and were used for joint QOL analysis. Trial-specific data including questionnaires at non-shared time-points were used for additional analyses. Intention-to-treat strategy was applied. Analyses were adjusted for baseline QOL, stage, performance status, gender, age, size of centre, trial, histotype and non-platinum companion drug. Results: Overall, 458/531 pts (86%) answered baseline questionnaire and missing rates over treatment were slightly higher among patients receiving cisplatin. Mean change in sore mouth after cycle 2 was worse with cisplatin ( P = 0.02). The size of differences between arms was in the small-medium range for peripheral neuropathy and alopecia (0.25 and 0.31 after one and 0.28 and 0.36 after two cycles, respectively) and for nausea/vomiting, sore mouth and dysphagia after two cycles (0.26, 0.38 and 0.25, respectively) always in the direction of worsening with cisplatin. Using a 10% change from baseline as clinically relevant threshold to categorize response, there was no significant difference between the arms. Time to deterioration of sore mouth and alopecia, with progression/death as competitive risk, was shorter with cisplatin (HR 1.72 95%CI 1.02–2.89, P = 0.04 and HR 1.84 95%CI 1.09–3.10, P = 0.02, respectively). Conclusion: The addition of cisplatin to single agent chemotherapy worsens sore mouth and alopecia and does not improve any QOL items in elderly patients with advanced NSCLC.